Ligands and characterization for effective bio‐atom‐transfer radical polymerization. Issue 1 (2nd January 2020) - Murata, Hironobu; Baker, Stefanie L.; Kaupbayeva, Bibifatima; Lewis, Dylan J.; Zhang, Libin; Boye, Susanne; Lederer, Albena; Russell, Alan J.
Abstract : Three new morpholine‐based ligands were synthesized and used in the ATRP reactions of free polymers and polymers grown from the surface of a protein in aqueous media. The new ligands were designed in a way that decreased their Lewis basicity with each additional incorporation of a morpholine group (1, 2, and 3). The morpholine‐based ligands significantly slowed the polymerization rates and led to lower dispersities than Et6 TREN. Increasing the control of aqueous ATRP correlated well with decreasing ligand basicity.